The Mechanical Behavior of Salt XI - Steven Sobolik; Mathew Ingraham; Edward Matteo; Melissa Mills; Tonya Ross; Donald Conley; John Stormont (CRC Press, 2025)
Rock salt formations have long been recognized as a valuable resource - not only for salt mining but for construction of oil and gas storage caverns and for isolation of radioactive and other hazardous wastes. Current interest is fast expanding towards construction and re-use of solution-mined caverns for storage of renewable energy in the form of hydrogen, compressed air and other gases. Evaluating the long-term performance and safety of such systems demands an understanding of the coupled mechanical behavior and transport properties of salt. This volume presents a collection of 83 research papers defining the state-of-the-art in the field. Topics range from fundamental work on deformation mechanisms and damage of rock salt to compaction of engineered salt backfill. The latest constitutive models are applied in computational studies addressing the evolution and integrity of storage caverns, repositories, salt mines and entire salt formations, while field studies document in situ salt behavior and conditions at multiple scales. The volume is structured into ten themes: Laboratory Testing Field and Geological Investigations Constitutive Modeling Modeling and Simulation Micromechanics and Microstructures Salt Caverns, Cavern Abandonment & Long-Term Integrity Crushed Salt Engineered Barriers Geological and Engineered Barriers Energy Storage and Mining Investigations Geological Storage of Hydrogen The Mechanical Behavior of Salt XI will appeal to graduate students, academics, engineers and professionals working in the fields of salt mechanics, salt mining and geological storage of energy and wastes, but also to researchers in rock physics in general.